From Ecotheology to Green Victimology: Bridging Faith-Based Environmental Ethics and Victim-Centered Legal Paradigms for Ecological Justice - Asmarani Ramli; Akhmad Jafar; Siti Malaiha Dewi; Indah Sri Utari; Farida Tuharea (Contemporary Issues on Interfaith Law and Society, 2026)
Global civilization is experiencing an unprecedented ecological crisis․ It is driven by extractive economic activity and projects such as the Merauke National Calculated Project in Indonesia‚ which promotes the establishment of an intensive sugarcane plantation covering an area of 560‚000 ha‚ posing a threat to biodiversity and Indigenous peoples․ The PGI (Communion of Churches in Indonesia) opposed the project‚ with ecotheological reasons․ Islamic thought also sees it as a duty to take care of nature‚ in the concept of khalifatul fil ardl (stewards of the earth). Morality and spirituality are incomplete without legal aspects․ Green victimology is introduced in this paper‚ a victim-centered legal study․ Green victimology goes beyond human victims and includes non-humans (trees‚ rivers‚ and other plants and animals) and ecosystems as victims of environmental crime․ Green victimology adopts normative legal research methods‚ using a theological-philosophical approach. The paper cites the Law Number 32/2009 concerning Environmental Protection and Management‚ Job Creation Law‚ PGI documents‚ Greenpeace reports‚ and classical theological sources of Islam and Christianity․ The results show that ecotheology provides the moral awareness and spiritual responsibility, while green victimology offers legal instruments and a victim-centered approach to tackle environmental destruction. Implementing this integration faces structural barriers in Indonesia's positivist legal system. This article, therefore, proposes an operational framework for granting religious communities locus standi in environmental advocacy and extends the ecological justice framework to global contexts. This article recommendation combined both ecotheology and green victimology to construct an ecological justice framework for addressing the spiritual and structural dimensions of environmental violence in Indonesia and beyond.